Usefulness of procalcitonin (PCT), C-reactive protein (CRP), and white blood cell (WBC) levels in the differential diagnosis of acute bacterial, viral, and mycoplasmal respiratory tract infections in children - Yang Li (BMC, 2021)
Abstract Background There is a lack of studies comparing PCT, CRP and WBC levels in the differential diagnosis of acute bacterial, viral, and mycoplasmal respiratory tract infections. It is necessary to explore the correlation between above markers and different types of ARTI. Methods 108 children with confirmed bacterial infection were regarded as group A, 116 children with virus infection were regarded as group B, and 122 children with mycoplasmal infection were regarded as group C. The levels of PCT, CRP and WBC of the three groups were detected and compared. Results The levels of PCT, CRP and WBC in group A were significantly higher than those in groups B and C (p < 0.05). The positive rate of combined detection of PCT, CRP and WBC was significant higher than that of single detection. There was no significant difference in PCT, CRP and WBC levels between the group of G+ bacterial infection and G− bacterial infection (p > 0.05). ROC curve results showed that the AUC of PCT, CRP and WBC for the diagnosis of bacterial respiratory infections were 0.65, 0.55, and 0.58, respectively. Conclusions PCT, CRP and WBC can be combined as effective indicators for the identification of acute bacterial or no-bacterial infections in children. The levels of PCT and CRP have higher differential diagnostic value than that of WBC in infection, and the combined examination of the three is more valuable in clinic.